2018
DOI: 10.1159/000490954
|View full text |Cite
|
Sign up to set email alerts
|

Trace Albumin in the Urine Dipstick Test is Associated with Coronary Artery Calcification in Korean Adults

Abstract: Background/Aims: Albuminuria is a risk factor for coronary artery calcification (CAC) and cardiovascular disease (CVD). Although the urine dipstick test is widely used to screen albuminuria, little is known about the association between low-grade urine dipstick albumin and CAC. The aim of this study is to investigate the relationship between the trace of urine dipstick albumin and CAC in Korean adults. Methods: This cross-sectional study analyzed 45,006 participants without previous CVD, who underwent coronary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…In clinical practice, detection and quantification of proteinuria are important in stratifying the risk for CKD progression and CVD [29]. In addition to being a prognostic marker, proteinuria is being considered as a therapeutic target in cardiovascular medicine [30].…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, detection and quantification of proteinuria are important in stratifying the risk for CKD progression and CVD [29]. In addition to being a prognostic marker, proteinuria is being considered as a therapeutic target in cardiovascular medicine [30].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have documented a strong association of albuminuria with the presence or development of CAD. As compared with normoalbuminuric individuals, people with albuminuria have increased severity of CAD 10 ; an association with high coronary artery calcium score 11 ; the presence of undetected, silent ischemia 12 ; low collateral vessel development in areas of CAD 13 ; and poorer outcomes after coronary artery bypass graft surgery. 14 , 15 One study demonstrated albuminuria to be a risk equivalent to prior myocardial infarctions.…”
Section: Association Of Albuminuria With Cardiovascular Diseasementioning
confidence: 99%
“…Compared with the negative group, the odds ratio (OR) for significant coronary artery calcium score was 1.62 (95% CI, 1.08–2.42) in the positive group and 1.34 (95% CI, 1.07–1.66) in the trace group. 11 In a prospective observational study, a random sample of 760 Japanese men from the general population without CVD or other severe diseases were followed up for an average of 5 years. 55 Coronary artery calcification progression was associated with albuminuria (UACR >30 mg/g) after adjustment for diabetes, hypertension, and CRP, independent of change in estimated glomerular filtration rate (eGFR; relative risk, 1.20 [95% CI, 1.01–1.43]; P =0.04).…”
Section: Association Of Albuminuria With Cardiovascular Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…The impact of albuminuria on atherosclerosis has been previously documented. Research conducted in Korea, involving 45,006 participants with no history of coronary artery calcification, revealed a connection between the existence of albuminuria and the presence of coronary artery calcification as determined through coronary computed tomog-raphy [78]. Additionally, findings from the TRACER trial [79] indicated that the presence of albuminuria correlated with a noteworthy rise in mortality among individuals experiencing acute coronary syndromes (HR: 1.65; 95% CI: 1.15-2.37).…”
Section: Albuminuria and Heart Failurementioning
confidence: 99%